2014
DOI: 10.1038/ng.2897
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide trans-ancestry meta-analysis provides insight into the genetic architecture of type 2 diabetes susceptibility

Abstract: To further understanding of the genetic basis of type 2 diabetes (T2D) susceptibility, we aggregated published meta-analyses of genome-wide association studies (GWAS) including 26,488 cases and 83,964 controls of European, East Asian, South Asian, and Mexican and Mexican American ancestry. We observed significant excess in directional consistency of T2D risk alleles across ancestry groups, even at SNPs demonstrating only weak evidence of association. By following up the strongest signals of association from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
744
3
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 975 publications
(784 citation statements)
references
References 52 publications
28
744
3
3
Order By: Relevance
“…Furthermore, the causal genetic variant and gene have not been identified for most of the detected loci. Previous studies have shown that variants associated with T2D in Europeans are largely transferable to other large populations such as the East and South Asian [17]. However, it is unknown whether the same alleles are associated with metabolic phenotypes in the Greenlandic population.…”
Section: Genetics Of Glycemic Traits -Similarities Between the Europementioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the causal genetic variant and gene have not been identified for most of the detected loci. Previous studies have shown that variants associated with T2D in Europeans are largely transferable to other large populations such as the East and South Asian [17]. However, it is unknown whether the same alleles are associated with metabolic phenotypes in the Greenlandic population.…”
Section: Genetics Of Glycemic Traits -Similarities Between the Europementioning
confidence: 94%
“…In the past decade, GWAS in large, open populations such as Europeans and Asians have proven highly successful in identifying common variants associated with complex diseases and traits, among them T2D and related metabolic traits [15][16][17][18][19][20]. Developments in genotyping and sequencing technologies have further enabled the study of lowfrequency and rare genetic variation [18,21,22].…”
Section: Gwas In Population Isolatesmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) found to be associated ( P  ≤ 5 × 10 −8 ) with T2D in two GWAS (comprising 38,840 cases and 114,981 controls [Morris et al, 2012] and 47,979 cases and 139,611 controls comprising a trans‐ancestry GWAS [Mahajan et al, 2014]) were used to perform MR by testing for their association with MDD and current psychological distress. The list consisted of 10 independently associated SNPs from DIAGRAM GWAS that were significant at a genome‐wide level [Morris et al, 2012], and seven further independent loci identified in the DIAGRAM trans‐ancestry T2D GWAS [Mahajan et al, 2014]. 11/17 SNPs were directly genotyped in GS:SFHS and these were the SNPs used in this study (Table II).…”
Section: Methodsmentioning
confidence: 99%
“…While this hypothesis has been debated 26,27 and assessed indirectly 3,28 , we used the near-complete ascertainment of genetic variation in 2,657 genome-sequenced individuals to directly test the importance of 'synthetic' associations 29 . We focused on the ten T2D GWAS loci at which our sample provided the strongest statistical evidence for association (p<0.001), implementing a conditional analysis procedure to assess whether combinations of SNVs within a 5Mb window could explain the common-variant signal (Extended Data Table 8; Methods).…”
Section: No Evidence For Synthetic Associationmentioning
confidence: 99%